Electron Collisions with Carbon Monoxide and Carbon Dioxide Moleculesat a Wide Range of Energies - Yassir, Ahlam K.; Khalaf, Alaa A. (Iraqi Journal of Science, 2025)
The present work displays a theoretical calculation of the differential, integral cross-sections, and momentum transfer of electrons scattering from carbon monoxide (CO) and carbon dioxide molecules (CO2). The collision energy used ranged from 20 to 1100 eV for the CO molecule and from 10 to 700 eV for the CO2 molecule. The partial wave analyses with complex optical model potential were used for solving the Dirac relativistic equation in the high and low energy regions. The results show decent agreement with current experimental studies and other theoretical predictions.